Mobile app for pedestrian and cyclist routes / Endrick Elong Erin and Asyraf Hakieme Hisammuddin - Elong Erin, Endrick; Hisammuddin, Asyraf Hakieme (Universiti Teknologi MARA (UiTM), 2024)
Earlier there was increase in Malaysians who use pedestrian and cyclist routes set aside and provided. This could arise as result of change in form and quality of public transport in society and or people’s changing perception on healthy living. The originally planned title for research is Mobile Application For Pedestrian And Cyclist Routes. It is mobile application that will help cyclists and pedestrians find routes to be used. This research was undertaken to achieve purpose of increasing rate of road safety for pedestrians and cyclists.